Using Webqual 4.0 and Importance Performance Analysis to Evaluate E-Commerce Website - Johanes Fernandes Andry; Kevin Christianto; Fuji Rahayu Wilujeng (Journal of Information Systems Engineering and Business Intelligence, 2019)
Background: The success of E-Business brings the highlight to websites as a tool to interact between company and customer. And recent studies indicate that quality of the website becomes something to be concern for company. Just like Huang pointed out that if company wants to build loyalty from their customer to get customer retention, one of much aspect that has to be noticed is the service quality from website.Objective: This study examines quality of website, such as Lazada. Website that author used in this research, to see what quality that website has and what the importance of that quality has. Methods: This study used Webqual 4.0 methodology to evaluate the website quality and see the importance of that quality using IPA (Importance Performance Analysis) to see how Lazada maintain that user expectations.Results: From three dimension that Webqual 4.0 provide for this research and total of 124 students as sample this research, authors found that all of three has significance result to satisfied customer with specific aspect on facilities, menus and contents from the website.Conclusion: Average respondent from students Bunda Mulia University was satisfied with the facilities, menus and contents in the web both from the value of all respondents and each research variable. The existing results from website user can be used as feedback on evaluation and development of Lazada website to be more accommodating to the wishes and in accordance with the expectations of website users.